A literature review on non-pharmacological treatments for irritable bowel syndrome (IBS) - Urban, Wojciech; Kornelia Karamus; Rafał Wojciech Rejmak; Jan Biłogras; Martyna Borowska-Łygan; Konrad Strużek; Jakub Tomaszewski (Journal of Education, Health and Sport, 2025)
Introduction Irritable bowel syndrome (IBS) is a prevalent condition involving the gut–brain interaction where individuals commonly experience recurring abdominal pain, changes in bowel movements, and frequently bloating. Aim The aim of this study was to review literature studies on IBS and non-pharmacological methods for treating this condition. Method Data for the article were retrieved by using Pub Med setting the time descriptor to 2019-2024. Conclusions Treating irritable bowel syndrome (IBS) continues to be challenging, as each patient needs a tailored approach. Once the correct IBS subtype is diagnosed, treatment should target the primary symptoms, such as bloating or diarrhea. Non-pharmacological treatment plays a initial, crucial and rapidly developing role in IBS therapy. Keywords Irritable bowel syndrome, non-pharmacological treatment, dietary, brain-gut axis, FODMAP